ANALISIS YURIDIS TERHADAP PENCEMARAN HUTAN MANGROVE PULAU PANNIKIANG DI KABUPATEN BARRU - Wahyu Rasyid, Nurhaedah Hasan, Hartono Hamzah, Syakiah (FAKULTAS HUKUM UM PAREPARE, 2022)
Mangrove forest ecosystems are natural resources that provide many benefits and advantages for humans, contributing to their high productivity and ability to preserve nature. Mangrove forests provide many ecological functions and that is why mangrove forests are one of the main producers of marine fisheries. The research entitled